A review of protection against exposome factors impacting facial skin barrier function with 89% mineralizing thermal water. (9th April 2019) - Salsberg, Jennifer; Andriessen, Anneke; Abdulla, Sonya; Ahluwalia, Renita; Beecker, Jennifer; Sander, Megan; Schachter, Jordana
Abstract: Background: The skin exposome refers to the constellation of external exposures that contribute to cutaneous aging, including solar radiation, air pollution, tobacco smoke, unbalanced nutrition, and cosmetic products. This review explores the skin exposome and the role of a combination hyaluronic acid and mineralized thermal water product used to restore and maintain optimal skin barrier function. Method: An expert panel of 7 dermatologists who treat clinical signs of facial aging convened for a one‐day meeting to discuss the results of a literature review on the skin exposome and the role of M89, a mineralized thermal water and hyaluronic acid‐based gel, to improve the quality of facial skin. Evidence coupled with expert opinion and experience of the panel was used to address clinical challenges in the treatment of photo‐aging, and the use of M89. Results: Solar radiation (ultraviolet radiation, visible light, and infrared radiation), air pollution, tobacco smoke, nutrition, and miscellaneous factors, including stress, sleep deprivation, and temperature, may potentiate skin aging by triggering molecular processes that damage skin structure. M89 was developed to maintain and restore skin and contains ingredients to aid physical, hydric, antioxidant, and antimicrobial skin barrier function. Conclusions: Increasing knowledge of the exposome and microenvironment contributing to skin aging may support a better understanding of measures to support the skin. The initial results of in vitro and clinical studies of M89 show its potential to improve skin barrier function.